2012
DOI: 10.1177/1087057111430124
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fluorescently Labeled Nrf2 Peptide Probes and the Development of a Fluorescence Polarization Assay for the Discovery of Inhibitors of Keap1-Nrf2 Interaction

Abstract: Activation of the antioxidant response element (ARE) up-regulates enzymes involved in detoxification of electrophiles and reactive oxygen species. The induction of ARE genes is regulated by the interaction between redox sensor protein, Keap1, and the transcription factor, Nrf2. Fluorescently labeled Nrf2 peptides containing the ETGE motif were synthesized and optimized as tracers in the development of a fluorescence polarization (FP) assay to identify small molecule inhibitors of Keap1-Nrf2 interaction. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 39 publications
6
115
3
Order By: Relevance
“…Briefly, a series of truncated NRF2 peptides was initially evaluated as direct inhibitors of PPI using surface plasmon resonance and fluorescence polarization assays (Hu et al, 2013). The minimal peptide sequence with inhibitory capacity was the 9-mer sequence of LDE-ETGE-FL (Chen et al, 2011;Inoyama et al, 2012). In parallel, Wells and collaborators (Hancock et al, 2013) searched for new putative peptide ligands using a phage display library combined with high-throughput fluorescence polarization assay.…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…Briefly, a series of truncated NRF2 peptides was initially evaluated as direct inhibitors of PPI using surface plasmon resonance and fluorescence polarization assays (Hu et al, 2013). The minimal peptide sequence with inhibitory capacity was the 9-mer sequence of LDE-ETGE-FL (Chen et al, 2011;Inoyama et al, 2012). In parallel, Wells and collaborators (Hancock et al, 2013) searched for new putative peptide ligands using a phage display library combined with high-throughput fluorescence polarization assay.…”
Section: B Protein-protein Interaction Inhibitors For Nuclear Factormentioning
confidence: 99%
“…The 14mer peptide 74 LQLDEETGEFLPIQ 87 experiences a drop in potency ( K D = 61.9 nM). 39 The 10mer peptide 76 LDEETGEFLP 85 , was less effective than the 16mer at inhibiting the complex ( K D = 30.1 nM) but still managed to displace Nrf2 from the complex. 39 Upon further deletion of residues from the 16mer peptide to increase its dynamic range, it was found that the 9mer 76 LDEETGEFL 84 ( K D = 352 nM) is the minimal Nrf2 peptide sequence required for the complex to be inhibited, as the 8mer peptide no longer bound to Keap1 with any affinity ( K D = ~1000 nM).…”
Section: Peptide- and Protein-based Nrf2 Activatorsmentioning
confidence: 97%
“…38 The ETGE motif has a higher affinity ( K D = 5 nM) than the DLG motif ( K D = 1 µM). 39,40 This difference in affinities stems from the motifs’ interactions with the pocket, detailed below.…”
Section: Nrf2/keap1 Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…FITC-β-EETGE E did not bind (K D >> 1000 nM), indicating a minimal recognition sequence of 6-7 amino acids [27]. Complementary assays based upon surface plasmon resonance [28,29], FRET [30], thermal denaturation [31], MS, NMR [32] and isothermal calorimetry [21] have also been applied to confirm ligand binding activity.…”
Section: Peptide Inhibitorsmentioning
confidence: 98%